The Taisirul Kholaq Book Approach in Forming the Honest Character of Students at the Al-Barokah Islamic Boarding School in Probolinggo Regency - Siti Aisyah; Khoiriyah Khoiriyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to describe the learning approach of the Taisirul Kholaq Book in shaping the honesty character of students at the Al-Barokah Islamic Boarding School in Probolinggo Regency. The background of this study is based on the phenomenon of weak implementation of honesty values among students even though honesty material has been taught textually and routinely in learning activities. This study uses a descriptive qualitative approach with a case study design. Data collection techniques include participatory observation, in-depth interviews, documentation, questionnaires, and focus group discussions (FGD). Data analysis was carried out using the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Taisirul Kholaq Book is implemented through contextual and narrative learning methods, supported by the exemplary role of ustadz and the Islamic boarding school environment that creates a positive moral climate. However, the internalization of honesty values is not optimal due to the rote approach, social pressure, and low affective involvement of students. This study recommends holistic learning that integrates cognitive, affective, and psychomotor aspects in a balanced manner.